In vitro susceptibilities of aerotolerant Campylobacter isolates to 22 antimicrobial agents. - Kiehlbauch, J A (1992)
We evaluated the in vitro activities of 22 antimicrobial agents against 78 human and animal isolates belonging to two aerotolerant Campylobacter species, C. cryaerophila and C. butzleri, using a broth microdilution technique. An additional 10 antimicrobial agents were included at concentrations found in selective Campylobacter media. Strains of C. cryaerophila belonged to two DNA hybridization groups: DNA hybridization group 1A, which includes the type strain of C. cryaerophila, and DNA hybridization group 1B. The aminoglycosides, fluoroquinolones, and one tetracycline (minocycline) demonstrated the most activity against all DNA hybridization groups (C. cryaerophila DNA groups 1A and 1B and C. butzleri). Most isolates were resistant to cephalosporin antibiotics, with the exception of cefotaxime, and were variably susceptible to trimethoprim-sulfamethoxazole. C. cryaerophila DNA hybridization group 1A isolates were generally susceptible to the tetracyclines, chloramphenicol, nalidixic acid, azithromycin, erythromycin, and roxithromycin and moderately susceptible to clindamycin, trimethoprim-sulfamethoxazole, ampicillin, and ampicillin-sulbactam. The MICs of tetracyclines were higher for C. butzleri and C. cryaerophila DNA hybridization group 1B isolates than for C. cryaerophila DNA hybridization group 1A isolates, but most strains were still susceptible to doxycycline and tetracycline; all isolates were susceptible to minocycline. C. butzleri and C. cryaerophila DNA hybridization group 1B isolates were generally resistant to the macrolide antibiotics (including erythromycin), chloramphenicol, clindamycin, nalidixic acid, ampicillin, and trimethoprim-sulfamethoxazole. Differences in antimicrobial susceptibility between aerotolerant Campylobacter species and more common Campylobacter species, e.g., C. jejuni, suggest that different treatment strategies may be necessary. Strains of all three DNA hybridization groups of aerotolerant Campylobacter isolates were susceptible to colistin, polymyxin B, and rifampin at concentrations commonly used in selective media. These results suggest that primary isolation methods for Campylobacter species may need to be modified to include aerotolerant Campylobacter strains.